2020
DOI: 10.3390/molecules25133000
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the Biosynthetic Potency of Taxol from Fungal Endophytes of Conifers Plants; Genome Mining and Metabolic Manipulation

Abstract: Endophytic fungi have been considered as a repertoire for bioactive secondary metabolites with potential application in medicine, agriculture and food industry. The biosynthetic pathways by fungal endophytes raise the argument of acquisition of these machineries of such complex metabolites from the plant host. Diterpenoids “Taxol” is the most effective anticancer drug with highest annual sale, since its discovery in 1970 from the Pacific yew tree, Taxus brevifolia. However, the lower yield of Taxol fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 162 publications
(340 reference statements)
1
54
0
Order By: Relevance
“…After tryptic digest, peptides were analyzed using liquid chromatography combined with tandem mass spectrometry (LC-MS/MS) and compared with the PL -cultured control using label-free quantification (LFQ) (Figure 2B) (Cox et al., 2014). We detected 15 PLP -DEs (GO term 0030170: PLP binding; Ashburner et al., 2000) significantly enriched upon PL1 labeling in HEK293 compared with the control (Figure 2C and Table S1), which accounts for around 30% of the complete human pool of PLP -binding enzymes (53 reviewed proteins annotated with GO term 0030170: PLP binding within the human proteome [UniProt: 9606]; Ashburner et al., 2000), including members of fold types I, II, and IV (El-Sayed and Shindia, 2012). Several PLP -DEs related to cancer proliferation and tumor development (e.g., SHMT1; Renwick et al., 1998 or cytosolic aspartate aminotransferase, GOT1; Thornburg et al., 2008) or to Parkinson disease (Bras et al., 2008) and atherosclerosis (Park et al., 2008) (serine palmitoyltransferase 2, SPTLC2, and sphingosine-1-phosphate lyase 1, SGPL1) were identified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After tryptic digest, peptides were analyzed using liquid chromatography combined with tandem mass spectrometry (LC-MS/MS) and compared with the PL -cultured control using label-free quantification (LFQ) (Figure 2B) (Cox et al., 2014). We detected 15 PLP -DEs (GO term 0030170: PLP binding; Ashburner et al., 2000) significantly enriched upon PL1 labeling in HEK293 compared with the control (Figure 2C and Table S1), which accounts for around 30% of the complete human pool of PLP -binding enzymes (53 reviewed proteins annotated with GO term 0030170: PLP binding within the human proteome [UniProt: 9606]; Ashburner et al., 2000), including members of fold types I, II, and IV (El-Sayed and Shindia, 2012). Several PLP -DEs related to cancer proliferation and tumor development (e.g., SHMT1; Renwick et al., 1998 or cytosolic aspartate aminotransferase, GOT1; Thornburg et al., 2008) or to Parkinson disease (Bras et al., 2008) and atherosclerosis (Park et al., 2008) (serine palmitoyltransferase 2, SPTLC2, and sphingosine-1-phosphate lyase 1, SGPL1) were identified.…”
Section: Resultsmentioning
confidence: 99%
“…PLP -DEs catalyze a diverse set of chemical reactions mainly with amino acid substrates, including decarboxylation, transamination, racemization, α , β , γ -substitution or α , β , γ -elimination (Percudani and Peracchi, 2003). Although sequence similarity is low among PLP -DEs, they are categorized into five distinct fold types guided by structural similarity (El-Sayed and Shindia, 2012). Due to the large number of chemical reactions catalyzed by PLP -DEs, they play a crucial role in cellular metabolism, ranging from amino acid biosynthesis and turnover to synthesis of neurotransmitters or tetrapyrroles (Parra et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This CFS was extracted with double volume of dichloromethane (DCM). The organic extract was then evaporated using a rotary evaporator (IKA, RV10, Staufen im Breisgau, Germany) at 35 °C; the dried residue was resuspended in 3 mL methanol and analyzed using the necessary chromatographic and spectroscopic methods [ 21 , 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…Total DNA was extracted from P. chrysogenum after its growth in potato dextrose broth (PDB) for 15 d [ 44 , 46 , 47 ]. The primers used for amplification of genes encoding 10-de-acetylbaccatin III-O-acetyltransferase (DBAT) that catalyze the immediate diterpenoid precursor of taxolwere5′-GGAGCCAATATGGAAGAGAGAAT-3′ as forward primer and 5′-TCCATG TTGCACGAGACTTAC-3′ as reverse primer (Promega Company, Madison, WI, USA) [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hicksii [1,2]. Most researchers have been devoted to studying on paclitaxel and its homologues from geuns Taxus owing to their outstanding anticancer effects [3].When it comes to bioflavonoids in Taxus, there's only a few research. However, several investigations have confirmed that biflavonoids has significant pharmacological activity, even though they are rare in nature and [4].…”
Section: Introductionmentioning
confidence: 99%